The essence of social capital in rural communities of migrants. Case study Tula, Tamaulipas, Mexico - Roberto Fernando Ochoa García; Jorge Alfredo Lera Mejía (Revista de Psicología y Ciencias del Comportamiento de la Unidad Académica de Ciencias Jurídicas y Sociales, 2019)
This essay discusses the issue of trust that affects the formation of social capital and its relationship with the use of remittances from migrant communities. The objective of this paper is to understand why having a strong social capital in binational migrant civil society, the citizen’s participation, trust and cohesion of in the use of collective remittances is not permeated among native land of the migrant's families, mainly in the municipalities with a high concentration of poverty and marginalization, the case of the municipality of Tula, Tamaulipas. In this regard, it is assumed that associations of organized migrants, are well cohesive and face the economic problems of their homeland, because even though they trust the authorities and public programs, migrants and their home town families, they do not have the confidence to create local networks due to lack of training and ignorance of public programs, nor the interest to participate in possible projects financed with remittances.